(untitled) (Revista científica Olimpia, 2015)
Physical education is an important element in the multilateral and harmonious child training. Their proper implementation is critical to the development of physical performance capacity of the individual, health maintenance and for the formation of moral and social values. However, for the treatment of those students with behavioral manifestations such as attention deficit in general primary school education, physical education professionals have limited knowledge and theoretical and methodological resources, to intervene to prevent the psycho procedures early-onset conduct disorder and in turn, negatively affects the learning of motor skills. A consideration of the author of the importance of the subject matter it is necessary to perform a bibliographic review of aspects related to attention deficit. For this information offered by digital sources and updated database on research to Physical Education and Sport, in different libraries in the province it was consulted.